Perspektif Hukum Islam Terhadap Perlindungan Data Pribadi Di Era Digital - Desy Damayanti; Rahma Hasna Naziha; Cucu Surahman (Yayasan Cendekia Gagayunan Indonesia, 2024)
The current digital era raises global issues on personal data protection, with many personal data leaks and weak legal frameworks. This research aims to explore the application of Islamic law to personal data protection by identifying challenges and opportunities. Descriptive qualitative method is used in this research to find out how Islamic values can be integrated in the legal framework of personal data protection. By collecting data through literature review and interviews, this study shows that the principles of Islamic law (maqasid al- sharia), emphasizing individual and public good provide a strong ethical and legal basis for the protection of personal data. However, integration with modern legal systems faces challenges, including low public awareness and technological gaps. Islamic legal principles such as hifzh al-'irdh and sadd dzari'ah have the potential to improve data protection policies, ensure fairness, and prevent harm in the digital age. The application of these principles offers a unique approach to creating a safer and more ethical digital culture. Islamic law provides an important contribution to the development of adaptive, ethical and comprehensive data protection policies, by encouraging collaboration between governments, communities and individuals.